Biclique‐based cryptanalysis of the block cipher SQUARE. Issue 3 (1st May 2014) - Mala, Hamid
Abstract : SQUARE, an eight‐round substitution‐permutation block cipher, is considered as a predecessor of the advanced encryption standard (AES). Recently, the concept of biclique‐based key recovery of block ciphers was introduced and applied to full‐round versions of three variants of AES. In this paper, this technique is applied to analyse the block cipher SQUARE. First, a biclique for three rounds of SQUARE using independent related‐key differentials has been found. Then, an attack on this cipher is presented, with a data complexity of about 2 48 chosen plaintexts and a time complexity of about 2 125.7 encryptions. The attack is the first successful attack on full‐round SQUARE in the single‐key scenario.